Peningkatan Proses Pembelajaran Tematik Terpadu dengan Menggunakan Model Discovery Learning di Kelas V Sekolah Dasar - Asnola Laili; Zaiyasni Zaiyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This study aims to describe the use of the Discovery Learning model to improve the integrated thematic learning process in the fifth grade of SD N 05 Bandar Buat Padang. This research is a classroom action research (CAR) that uses a qualitative and quantitative approach. Conducted in two cycles, with three meetings covering four stages, namely planning, implementation, observation, and reflection. The subjects of this study were researchers, teachers, and fifth grade students of SD N 05 Bandar Buat Padang, totaling 27 people. The results of the study were: (1) the percentage of lesson plan observation was 78.12%, an increase of 93.75%. (2) Teacher activities 79.7%, an increase of 90.6%. (3) Student activities 79.7%, an increase of 90.6%.